Determinan Stres Postpartum pada Ibu: Analisis Jalur Faktor Sosiodemografi dan Adaptasi Psikologis - Irfa Nur Faujiah; Shiva Aflahiyah; Alvin Alvani Tresna Ambari (Jurnal Kebidanan Indonesia, 2026)
Background: Postpartum stress is a psychological problem frequently experienced by mothers during the postpartum period and may affect maternal well-being, infant care, and family functioning. Sociodemographic conditions and the mother’s ability to psychologically adapt are considered important factors influencing postpartum stress. Objective: This study aimed to analyze the relationship between sociodemographic factors and psychological adaptation ability toward postpartum stress among postpartum mothers. Method: This study used an observational analytic design with a cross-sectional approach. A total of 150 postpartum mothers from five villages in the Singaparna Health Center area were selected using purposive sampling. Data were collected using a sociodemographic questionnaire, the Perceived Stress Scale (PSS), and the Postpartum Adjustment Questionnaire (PAQ). Data analysis included univariate analysis, Kolmogorov–Smirnov normality test, Spearman correlation, and path analysis. Results: The results showed that employment status had a significant relationship with postpartum stress (r = -0.213; p = 0.009). Psychological adaptation ability was also significantly associated with postpartum stress (r = 0.254; p = 0.002). Path analysis indicated that employment status directly influenced postpartum stress (b = -3.228; p = 0.004), while psychological adaptation ability also had a direct effect on postpartum stress (b = 0.102; p = 0.001). Educational level significantly influenced psychological adaptation ability indirectly (b = 2.682; p = 0.047). Conclusion: Psychological adaptation ability plays an important role in postpartum stress among postpartum mothers. Strengthening maternal psychological adaptation and psychosocial support during the postpartum period is necessary to reduce postpartum stress.